An electroporation platform for Erlotinib resistance screening in living non-small cell lung cancer (NSCLC) cells. (10th January 2018) - Yan, Z; Hui, T H; Fong, H W; Shao, X; Cho, W C; Ngan, K C; Yip, T C; Lin, Y
Abstract: An electroporation device was developed to introduce transient membrane pores and, consequently, enhance membrane permeability in living cells in a controllable manner. The validity of this platform was assessed on six non-small cell lung cancer (NSCLC) cell lines using different fluorescent dyes. Interestingly, it was found that the electroporation efficiency of these cells, i.e. the percentage of cells with membrane pores created, decreases significantly (from ∼60% to 30%) as their resistivity against Erlotinib increases, demonstrating the potential of such approach as a screening tool for assessing drug resistance in tumours in the future. Furthermore, we showed that the inverse relationship between the electroporation efficiency and Erlotinib resistance is likely due to the fact that NSCLC cell lines with higher drug resistivity appear to have lower cortical tensions and hence make it harder for membrane pores to be created, consistent with existing electroporation theories.